Clinical impact and early prediction of carbapenem-resistant Pseudomonas aeruginosa bacteraemia in allogeneic hematopoietic stem cell transplantation recipients. (March 2023) - Sakaguchi, Masahiro; Atsuta, Yuya; Sekiya, Noritaka; Najima, Yuho; Fukushima, Kazuaki; Shingai, Naoki; Toya, Takashi; Kobayashi, Takeshi; Ohashi, Kazuteru; Doki, Noriko
Highlights: We evaluated P. aeruginosa bacteraemia in allogeneic stem cell transplant recipients. Carbapenem-resistant (CR) P. aeruginosa were the focus of the present study. Mortality was higher in CR compared with carbapenem-sensitive (CS) P. aeruginosa . Carbapenem exposure (≥ 3 days) was associated with CR P. aeruginosa bacteraemia. Inappropriate antimicrobial selection was frequent in CR P. aeruginosa bacteraemia. ABSTRACT: Objective: Although antipseudomonal agents are administered in high-risk patients, no reports have focused on the risk of carbapenem-resistant (CR) Pseudomonas aeruginosa bacteraemia in allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients. Methods: We retrospectively studied a cohort of adult allo-HSCT recipients with P. aeruginosa bacteraemia, focusing on a comparison between carbapenem-sensitive (CS) and CR P. aeruginosa after initiating conditioning chemotherapy at our institute between January 2005 and December 2020. The incidence, all-cause 30-d mortality of P. aeruginosa bacteraemia, and risk factors for carbapenem resistance among patients with P. aeruginosa bacteraemia in allo-HSCT recipients were evaluated. Results: Forty-eight patients with P. aeruginosa bacteraemia were included, with an incidence of 3.84/100 recipients (CS = 1.92 vs. CR = 1.92). The all-cause 30-d mortality was significantly higher in CR P. aeruginosa bacteraemia (CS = 4.2% vs. CR = 39.1%; P = 0.003). The factor significantly associated with CR P. aeruginosa bacteraemia was carbapenem use for at least 3 d within 30 d before the onset of bacteraemia (odds ratio = 8.92; 95% confidence interval: 1.35–58.90). Inappropriate antimicrobial selection was significantly more frequent in CR P. aeruginosa bacteraemia (CS = 0% vs. CR = 29.2%; P ˂ 0.009). Conclusion: Empirical combination therapy with reference to antimicrobial susceptibility profiles in each institution should be considered when CR P. aeruginosa bacteraemia is suspected in allo-HSCT recipients based on the risk of carbapenem exposure.